2021
DOI: 10.2147/jir.s331727
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphism LncRNA AC008392.1/rs7248320 in CARD8 is Associated with Kawasaki Disease Susceptibility in the Han Chinese Population

Abstract: Background Kawasaki disease (KD) is a multisystem vasculitis in infants and young children and involved in the NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome activation. Genetic factors may increase the risk of KD. To assess the association between rs7248320 in long noncoding RNA (lncRNA) AC008392.1 located in the upstream region of CARD8 and the risk of KD, a case–control study was conducted in the Han Chinese population. Methods This study ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Kawasaki disease (KD), a mucocutaneous lymph node syndrome named after its discoverer (Kawasaki), is an acute febrile inflammatory disease that tends to occur among infants and children [ 1 , 2 ]. KD is the most common cause of acquired heart disease in children in developed countries and even leads to coronary artery aneurysms (CAA), elevating the risk of coronary artery thrombosis in the later stage [ 3 ]. In addition, the main clinical presentations of KD include persistent fever, pleural rash, conjunctival congestion, oral mucosal lesions, swollen neck lymph nodes, and severe hand swelling, which seriously threaten children's physical and mental health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kawasaki disease (KD), a mucocutaneous lymph node syndrome named after its discoverer (Kawasaki), is an acute febrile inflammatory disease that tends to occur among infants and children [ 1 , 2 ]. KD is the most common cause of acquired heart disease in children in developed countries and even leads to coronary artery aneurysms (CAA), elevating the risk of coronary artery thrombosis in the later stage [ 3 ]. In addition, the main clinical presentations of KD include persistent fever, pleural rash, conjunctival congestion, oral mucosal lesions, swollen neck lymph nodes, and severe hand swelling, which seriously threaten children's physical and mental health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of KD is still unclear, and many association studies have identified that the lncRNAs PINC, SOCS2-AS1, SRA, HCG22, MHRT and AC008392.1 may modify the occurrence of KD and may even be related to CAL complications. 24,[30][31][32] So far, no study report has explored the association of the lncRNA rs1814343 C > T polymorphism with the susceptibility to KD. Studies have shown that lncRNAs play major roles in cardiovascular disease because lncRNAs can regulate the development of cardiovascular disease by regulating the growth and function of vascular endothelium and the migration/ differentiation of vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of KD is still unclear, and many association studies have identified that the lncRNAs PINC, SOCS2‐AS1, SRA, HCG22, MHRT and AC008392.1 may modify the occurrence of KD and may even be related to CAL complications 24,30–32 . So far, no study report has explored the association of the lncRNA rs1814343 C > T polymorphism with the susceptibility to KD.…”
Section: Discussionmentioning
confidence: 99%
“…The long noncoding RNA (LncRNA) AC008392.1 gene is located in the long arm of chromosome 19 upstream of CARD8, and it is known that it expresses in several cell lines such as B cells and tumor cells (K. Guo et al, 2021; Lv et al, 2018; Yin et al, 2015). CARD8 is a component of the NLRP3 inflammasome that inhibits NLRP3 inflammasome activation, which is one of the main drivers of KD vasculitis (Takahashi, 2022; Wang et al, 2021).…”
Section: Nlrp3 and Kdmentioning
confidence: 99%
“…Moreover, several studies have revealed the important link of CARD8 polymorphisms with inflammation‐related diseases such as rheumatoid arthritis (Kastbom et al, 2010), atopic dermatitis (Bivik et al, 2013), Crohn's disease (Z. T. Zhang et al, 2015), and gout (Y. Chen, Ren et al, 2015). Based on these shreds of information, K. Guo et al (2021) designed a case‐control study to investigate the association of rs7248320 in AC008392.1 and susceptibility to KD. They found that rs7248320 polymorphism significantly reduces the risk of KD after sex and age adjustment.…”
Section: Nlrp3 and Kdmentioning
confidence: 99%